2013
DOI: 10.1007/s00586-013-2897-z
|View full text |Cite
|
Sign up to set email alerts
|

Cervical arthroplasty with Discover prosthesis: clinical outcomes and analysis of factors that may influence postoperative range of motion

Abstract: Purpose The aim of this current study was to analyze the clinical outcomes after Discover cervical disc replacement and its effects on maintaining cervical lordosis and range of motion (ROM). The possible factors influencing postoperative ROM were analyzed. Method 27 men and 28 women with a mean age of 46.4 ± 8.7 years were prospectively followed up for 2 years. Clinical outcomes were assessed using Japanese Orthopedic Association (JOA), Neck Disability Index (NDI), visual analog scale (VAS) and Odom's criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…The results of this study demonstrated promising clinical and radiological outcomes. Concerning the NDI the observation showed a significant improvement of 51.5 % ( p < 0.001) after implantation which correlates with present studies of other available cervical disc prosthesis [ 4 6 ]. Analysis of VAS showed a significant reduction of neck and arm pain early after surgery which might primarily be related to sufficient decompression during surgery and the in-hospital pain management.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study demonstrated promising clinical and radiological outcomes. Concerning the NDI the observation showed a significant improvement of 51.5 % ( p < 0.001) after implantation which correlates with present studies of other available cervical disc prosthesis [ 4 6 ]. Analysis of VAS showed a significant reduction of neck and arm pain early after surgery which might primarily be related to sufficient decompression during surgery and the in-hospital pain management.…”
Section: Discussionsupporting
confidence: 91%
“…According to prior clinical trials of cervical arthroplasty subsequent secondary surgical intervention was defined as any revision, removal, reoperation or supplemental fixation [ 1 , 4 6 ]. Until the last follow-up in one case (2.2 %) an increase of neck and arm pain was observed and subsequent secondary surgical intervention was required to remove a probably undersized prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 None of the patients in this study had any neurological impairment, and the decision to undergo revision surgery was due to the results of this motion analysis, showing highly instable implants, in combination with increased neck pain. A previously published motion study of the same artificial disc reported migration in 6 of 55 patients (11%), 10 although evaluations were done with plain radiographs. Other previous radiographic studies on other artificial discs have not reported similar figures concerning loosening or migration to the same extent.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время тотальная артропластика МПД, как современный альтернативный способ хирургического лечения дегенеративного заболевания МПД, набирает все большую популярность во многих нейрохирургических клиниках мира [5,6]. Целью артропластики МПД являются полное восстановление и поддержание физиологического объема движений в позвоночно-двигательном сегменте, что позволяет предотвратить дегенерацию смежных МПД, нивелировать болевой синдром и неврологическую симптоматику [7].…”
Section: Analysis Of the Results Of Total Cervical Disc Arthroplasty unclassified